The term structure of liquidity provision - Conrad, Jennifer; Wahal, Sunil (Journal of Financial Economics, 2020)
We examine realized spreads and price impact in clock and trade time following each trade in all common stocks from 2010 to 2017. The term structure of realized spreads (price impact) is sharply downward (upward) sloping, implying that (a) market maker profitability is sensitive to speed, and (b) the choice of the horizon of measurement is critical when drawing inferences from spread decompositions. The majority of the price impact of trades in large (small)-capitalization stocks takes place within 15 (60) seconds. Net profits to liquidity provision, or equivalently, net costs to liquidity demanders, decline over the sample period even at the shortest horizons that we consider: at the 100 ms horizon, aggregate profits decline from 1.9 basis points of total dollar volume in 2010 to 1.0 basis points in 2017.